Trade, traders and the ancient city - Parkins, Helen, 1966-; Smith, Christopher John, 1965- (London ; New York : Routledge, 1998)
Trade, exchange and commerce touched the lives of everyone in antiquity, especially those who lived in urban areas. Trade, Traders and the Ancient City addresses the nature of exchange and commerce and the effects it had in cities throughout the ancient world, from the Bronze Age Near East to late Roman northern Italy. Trade, Traders and the Ancient City employs the most recent archaeological, papyrological, epigraphic and literary evidence to present an innovative and timely analysis of the importance and influence of trade in the ancient world.
1. Time for change? Shaping the future of the ancient economy / Helen Parkins -- 2. The old Assyrian merchants / Amélie Kuhrt -- 3. Traders and artisans in archaic central Italy / Christopher Smith -- 4. Trade on the Black Sea in the archaic and classical periods : some observations / Gocha R. Tsetskhladze -- 5. Ceramics and positivism revisited : Greek transport amphoras and history / Mark Lawall -- 6. The grain trade of Athens in the fourth century BC / Michael Whitby -- 7. Land transport in Roman Italy : costs, practice and the economy / Ray Laurence -- 8. Trade and traders in the Roman world : scale, structure, and organisation / Jeremy Paterson -- 9. Trade and the city in Roman Egypt/ Richard Alston -- 10. Trading gods in northern Italy / Mark Humphries -- 11. Ancient economies : models and muddles / John K. Davies.
A collection of papers from a 1995 conference with the same working title.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Commerce -- History -- To 500 -- Congresses; Trade routes -- History -- Congresses; Cities and towns, Ancient -- History -- Congresses; Economic history -- To 500 -- Congresses; Assyria -- Commerce -- History -- Congresses; Rome -- Commerce -- History -- Congresses; Greece -- Commerce -- History -- Congresses; Commerce -- Histoire -- Jusqu'à 500 -- Congrès.; Routes commerciales -- Histoire -- Congrès.; Villes antiques -- Histoire -- Congrès.; Histoire économique -- Jusqu'à 500 -- Congrès.; BUSINESS & ECONOMICS -- International -- Marketing; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- Exports & Imports; Cities and towns, Ancient; Commerce; Economic history; Trade routes; Greece; Middle East -- Assyria; Rome (Empire); To 500; Electronic books; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings; Actes de congrès.